The Pselaphinae (Coleoptera: Staphylinidae) of New Caledonia and Loyalty Islands. IV. Revision of the genus Baraxina Raffray, 1896 - Hlaváč, Peter; Jałoszyński, Paweł (Zootaxa, 2021)
The endemic New Caledonian Brachyglutini genus Baraxina is revised. Seventeen species are recognized, of which sixteen are newly described: B. francoisi Raffray, 1886; B. amieuana sp. n., B. grimbacheri sp. n., B. kanakorum sp. n., B. rutai sp. n., B. aoupinica sp. n., B. asymmetrica sp. n., B. burwelli sp. n., B. dzumacana sp. n., B. jenisi sp. n., B. koghisiana sp. n., B. lescheni sp. n., B. monteithi sp. n., B. parakoghisiana sp. n., B. pecki sp. n., B. poroana sp. n., and B. wanati sp. n.